MFAP5 inhibits the malignant progression of endometrial cancer cells in vitro - Liang Guanying; Qi Zijuan; Du Chun (Open Life Sciences)
To investigate the biological role of MFAP5 in endometrial cancer (EC). HEC-1-A and Ishikawa cells overexpressing MFAP5 were created. Cell proliferation, apoptosis, migration, and invasion were evaluated using CCK8, colony formation, flow cytometry, and transwell assays. A western blot was used to analyze the expression of markers affiliated with the epithelial–mesenchymal transition process and AKT/mTOR pathway. As a result, MFAP5 was found to be down-regulated in EC. Overexpression of MFAP5 suppressed proliferation and promoted apoptosis of HEC-1-A and Ishikawa cells, as evidenced by the inhibition of cell viability and colony formation, and the increase in cell apoptosis rate. Besides, overexpression of MFAP5 attenuated the abilities of cell migration and invasion, as well as reduced MMP2 and MMP9 protein expression. Furthermore, E-cadherin protein level was elevated, while N-cadherin and α-SMA protein levels were decreased, and the phosphorylation of AKT and mTOR was reduced in cells overexpressing MFAP5. Our findings indicate that MFAP5 overexpression inhibits the malignant behaviors of EC cells, possibly by blocking the AKT/mTOR pathway, suggesting that MFAP5 may be a new therapeutic target for EC.